An update on the regulation of photosynthesis by thylakoid ion channels and transporters in Arabidopsis. Issue 1 (9th June 2017) - Spetea, Cornelia; Herdean, Andrei; Allorent, Guillaume; Carraretto, Luca; Finazzi, Giovanni; Szabo, Ildikò
Abstract : In natural, variable environments, plants rapidly adjust photosynthesis for optimal balance between light absorption and utilization. There is increasing evidence suggesting that ion fluxes across the chloroplast thylakoid membrane play an important role in this regulation by affecting the proton motive force and consequently photosynthesis and thylakoid membrane ultrastructure. This article presents an update on the thylakoid ion channels and transporters characterized in Arabidopsis thaliana as being involved in these processes, as well as an outlook at the evolutionary conservation of their functions in other photosynthetic organisms. This is a contribution to shed light on the thylakoid network of ion fluxes and how they help plants to adjust photosynthesis in variable light environments.